(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Background: There is a two way relationship between disease and malnutrition. The consequences of malnutrition during formative early years can extend long beyond the disease itself, necessitating the interception of this continuous cycle. Objective: To assess the nutritional status of children having chronic diarrhea Materials and Methods: The study was a cross–sectional survey. A purposive sample of 50 chronic diarrhea patients between 1-3 years of age was collected from pediatric outdoor patient department, Sir Ganga Ram Hospital, Lahore. Anthropometric data (height and weight) was compared to the reference population in terms of key malnutrition indices. The data was then analyzed for the frequency as well as severity of malnutrition in the study sample. Results: Sixty eight percent of the sample was found to be underweight, 56% wasted and 64% stunted. The proportion of severely malnourished individuals (<-3 S.D.) was greater than those who scored <-2 S.D. Severe malnutrition was found to be linked to onset of chronic diarrhea at an early age. Conclusions: Key anthropometric indices showed malnutrition to be quite prevalent in the sample. The findings suggest a possible link between diarrhea and malnutrition. Nutritional interventions are, therefore, recommended as an important component of health care of such children.